Vagueness and Ambiguity in Communication of Case Management: A Content Analysis in the Australian National Disability Insurance Scheme - Lukersmith, Sue (Int J Integr Care, 2021)
Case management (CM) is an integrated care strategy, characterised by a set of actions to support person-centred planning, coordination of health and social services. Decades of CM, organisational psychology and occupational research highlight how vagueness and ambiguity in role communication can create role conflict and job stress, negatively impacts staff turnover, intra-organisational collaboration, job performance, and that poor communication of CM impedes policy, quality analysis service development and practice. We conducted a detailed top-down hierarchical, quality analysis of communication about CM roles and responsibilities in a Scheme for people with disability in Australia. The study used content analysis methods and the main actions as defined in a validated CM taxonomy (Appendix 1). We systematically searched and analysed 53 Scheme policy and practice documents of CM from 2013–2019. The results showed poor role communication with vagueness, ambiguity, gaps in the description of CM roles and responsibilities. Poor role communication has contributed to negative experiences and outcomes of CM actions of planning and coordination, as reported by CM users in many Scheme-related parliamentary inquiries, research, formal complaints, and decision appeals. The results reinforce the importance of an ontological approach in communication of CM roles and actions and provides learnings for integrated care roles across countries and contexts.